2013
DOI: 10.1002/dev.21098
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic concordance in mother and preschooler resting cardiovascular function varies by risk status

Abstract: This study examined concordance in heart rate (HR) and respiratory sinus arrhythmia (RSA) in a sample of 104 child-maltreating (CM) and nonCM mother–preschooler dyads (208 individuals). In a laboratory setting, mother and child cardiac physiology was simultaneously monitored via ECG in a 5-min resting period. Mothers ranged in age from 20 to 49 years; children ranged in age from 3 to 5 years. Significant within-dyad (WD) and between-dyad (BD) associations were observed for mother HR and both child HR and RSA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
119
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(136 citation statements)
references
References 41 publications
16
119
0
1
Order By: Relevance
“…Feldman and colleagues (2011) found a time-lagged heart rhythm concordance between low-risk mothers and their 4-month-old infants. Likewise, we have observed significant concordance in mother and preschooler contemporaneously measured resting HR and RSA, such that greater maternal HR was associated with greater child HR and lower child RSA (Creaven, Skowron, Hughes, Howard, & Loken, 2014). In a prospective study of 76 mother–infant dyads, Bornstein and Suess (2000) found no associations between mothers and children at 2 months or at 5 years in either resting HR or RSA, although RSA withdrawal in response to challenge showed positive between-dyad associations by age 5.…”
Section: Introductionsupporting
confidence: 53%
“…Feldman and colleagues (2011) found a time-lagged heart rhythm concordance between low-risk mothers and their 4-month-old infants. Likewise, we have observed significant concordance in mother and preschooler contemporaneously measured resting HR and RSA, such that greater maternal HR was associated with greater child HR and lower child RSA (Creaven, Skowron, Hughes, Howard, & Loken, 2014). In a prospective study of 76 mother–infant dyads, Bornstein and Suess (2000) found no associations between mothers and children at 2 months or at 5 years in either resting HR or RSA, although RSA withdrawal in response to challenge showed positive between-dyad associations by age 5.…”
Section: Introductionsupporting
confidence: 53%
“…In addition, when parents are less able to regulate their own physiological responses, synchronous coregulation patterns that support successful child selfregulation may become weaker, or possibly divergent. For example, mothers who exhibited elevated heart rates showed less physiological synchrony with their children (Creaven et al, 2014), whereas mothers who showed RSA withdrawal during a stressful interaction displayed greater behavioral synchrony with children (Giuliano, Skowron, & Berkman, 2015). Such results suggest that individual parent factors, such as physiological responding and behavioral engagement, are important in promoting synchrony in parent-child coregulation.…”
Section: Parent-child Coregulationmentioning
confidence: 96%
“…Parents who have had a history of maltreatment of their children, including physical or emotional abuse and neglect, also demonstrate coregulatory patterns with their children that are divergent, or tend to move away from one another over time (Creaven, Skowron, Hughes, Howard, & Loken, 2014). In addition, when parents are less able to regulate their own physiological responses, synchronous coregulation patterns that support successful child selfregulation may become weaker, or possibly divergent.…”
Section: Parent-child Coregulationmentioning
confidence: 99%
“…Research into relational trauma undertaken by Elizabeth Skowron and colleagues at the University of Oregon has clearly demonstrated that levels of DoS are indicative of child abuse risk, impaired rupture and repair processes, reduced positive autonomy support, and resiliency in children who experience family violence and physiological indicators of impulse control such as respiratory sinus arrhythmia which is a marker of increased risk of harm by a caregiver to a child (Cipriano, Skowron, & GatzkeKopp, 2011;Creaven et al, 2014;Lunkenheimer, Ram, Skowron, & Yin, 2017;Skowron & Dendy, 2004;Skowron, Kozlowski, & Pincus, 2010;Skowron & Platt, 2005).…”
Section: Enhancing Therapist Resiliencymentioning
confidence: 99%